2022
DOI: 10.21203/rs.3.rs-2247354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparison study of different grasses on agronomic performance and chemical composition across three altitudes and harvesting dates in Ethiopia

Abstract: One of the major limiting factors of livestock production in Ethiopia is the very low quantity and quality of livestock feeds supplied in the country. This calls for seeking forages that complement poor quality feeds in the country. Hence, this research project was accomplished to comparatively evaluate and find compatible forages among three types of grass. The target of this paper was to compare three types of grass agronomic performance and chemical composition under three different agro-ecologies and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Generally, the recent study in the studied areas revealed that Brachiaria hybrid cv. Mulato II grass adapted well and had higher yield and nutritive values than other Brachiaria ecotypes [52], Brachiaria cultivars (Marandu and La Librtad) [53]. Te signifcant diference among grasses in chemical composition due to interaction shows that the performances of grasses vary according to agro-ecologies and harvesting dates.…”
Section: Discussionmentioning
confidence: 94%
“…Generally, the recent study in the studied areas revealed that Brachiaria hybrid cv. Mulato II grass adapted well and had higher yield and nutritive values than other Brachiaria ecotypes [52], Brachiaria cultivars (Marandu and La Librtad) [53]. Te signifcant diference among grasses in chemical composition due to interaction shows that the performances of grasses vary according to agro-ecologies and harvesting dates.…”
Section: Discussionmentioning
confidence: 94%